Analysis of Genetic Alterations in Cutaneous Malignant Melanomas Unveils Unique Loco-Regional Variations and Novel Predictors of Metastatic Potential. (December 2021) - Krishnamurthy, Kritika; Urioste, Sophia N.; Cusnir, Mike; Schwartz, Michael; Alghamdi, Sarah; Sriganeshan, Vathany; Poppiti, Robert
Abstract : Abstract: Cutaneous malignant melanoma is an aggressive cancer that contributes significantly to cancer-related mortality. Over the years, a deeper scrutiny of melanoma biology has led to identification of diverse evolutionary patterns involving various genetic pathways. This study attempts to further understand the genetic landscape of cutaneous malignant melanoma in terms of loco-regional variations and malignant potential. Thirty-five cases of cutaneous malignant melanoma were retrieved from the archives and were classified based on location of the primary tumor and presence or absence of metastatic disease. Next-generation sequencing data consisting of base substitutions, copy number variations, indels, and rearrangements in a total of 324 genes were analyzed for recurrent genetic alterations. Statistical analysis was performed using IBM SPSS26 software. Mutations in KDM gene family were found in 62.5% of the melanomas in the head and neck as compared with 10% in melanomas of the extremity and trunk ( P = 0.03). Mutations in the RAS gene family were found in 70% of melanomas in the extremities as compared to 12.5% in melanomas of the head and neck ( P = 0.003). BTK gene mutations were found exclusively in melanomas of the head and neck ( P = 0.032). CREBBP mutations were seen in 50% of the nonmetastatic melanomas as compared with 3.57% of metastatic melanomas ( P = 0.005). This study highlights the loco-regional variations in cutaneous malignant melanoma for genetic alterations involving the KDM, RAS, and BTK gene family. In addition, the CREBBP mutational status is identified as a potential prognostic marker for predicting metastatic potential in cutaneous malignant melanomas.